Severe Cardiorespiratory and Neurologic Symptoms in a Neonate due to Mepivacaine Intoxication - Maurike de Groot-van der Mooren; Sabine Quint; Ingmar Knobbe; Doug Cronie; Mirjam van Weissenbruch (Hindawi Limited, 2019)
Local anesthesia with mepivacaine is used for vaginal deliveries and for minor surgeries of the vagina and perineum as repair of an episiotomy or perineal laceration. Neonatal intoxication caused by local anesthesia with mepivacaine for maternal episiotomy has been rarely reported. We present a case of a term female infant with unexplained cardiorespiratory distress and several neurologic findings, including seizures, one hour after birth. Electrocardiogram showed a second-degree atrioventricular block and a left-bundle branch block. Blood measures in the patient revealed a high mepivacaine level following local anesthesia for maternal episiotomy. Because of the increasing practice of local anesthesia, high awareness for neonatal intoxication and further research in safe elimination therapy in neonates is needed.